The Cost of a "Beveridge Plan" in the United States - Klein, Lawrence R. (Quarterly Journal of Economics, 1944)
Significance of the question, 423. — The structure of an American Plan, 424. —The major assumptions: population growth and levels of employment, 428. — Basis of the estimates, 429. — Comparison with existing public aid programs and national income, 434. — Comparison with proposed American plans, 435.